The concept of the sharing economy - a view from different perspectives - Podrug, Doris (Oeconomica Jadertina, 2023)
The rapid technological development of the past few decades has led to a shift away from traditional business models toward new models that rely on digital platforms to share underutilized goods or services. This phenomenon is known as the sharing economy, and it is significantly changing the consumer behaviour of millions of people worldwide. The expansive growth of the sharing economy and its dramatic impact on various aspects of today’s socio-economic system have fuelled increasing public interest in the last ten years. Many new players have entered the market in various fields, gaining significant importance, and some have even overtaken existing players. The sharing economy significantly changes business models in different industries and poses numerous economic, social, and legal issues. The aim of this paper is to identify trends in the development of the sharing economy concept, provide an exhaustive analysis of current knowledge through a review of relevant literature, and explore potential unexplored areas of the sharing economy. To this end, the paper offers an overview of the literature on the motivation and experiences of users, the influence of reviews on service selection, and the factors that influence pricing. In addition, the paper examines the motivation for participation, strategies, and behaviour of service providers. The paper underscores the importance of studying all sectors and platforms in the sharing economy, given that the largest number of studies to date relate to the area of accommodation.
Keywords: sharing economy, collaborative consumption, service user aspect, service provider aspect, Airbnb